The Cultural Industries: Virtuoso Worker and the Labor Entrance of Language - Gutiérrez, Jairo Rafael (Disertaciones, 2026)
This article proposes a philosophical conceptualization of cultural industries as a socioeconomic and biopolitical category, approached from a critical hermeneutic perspective. Drawing on the contributions of Paolo Virno, post-operaist Antonio Negri, and situationist Guy Debord, it argues that cultural industries not only generate employment and creativity, but also shape new forms of immaterial labor based on communication skills and competencies. The central thesis argues that these industries act as a biolinguistic expression of biopolitics, influencing the affections and emotions of individuals through financial signs disseminated by the media. The figure of the “virtuous worker,” protagonist of contemporary capitalism, whose value lies in linguistic and cognitive production rather than material goods, is examined. Finally, it reflects on the relationship between language and economics, showing how communication becomes a commodity and the driving force behind the global productive fabric.